RELATION OF HOUSE OF REPRESENTATIVES / REGIOMAL PEOPLES’S REPRESENTATIVE ASSEMBLY WITH ROLE OF POLITICAL PARTIES IN THE ERA OF REFORM IN INDONESIA - Benjamin Tungga; Francis Xavier Wartoyo (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
The idea to highlight and expose the dualism and impartiality of parliament members, either regionally and / or at national level, against Reviews their play jobs, functions, and roles as the members of any given political party was the first that Came to mind at the onset of writing this paper. Upon digging The Necessary information and materials, the main theme of this paper shifts to reveal that the election has Become a means to gain the position as the ruler that legalized and legitimate.Voters can choose directly Reviews their intended candidates as the winning one.As is the case, the loose ends of a regional unhappy residents growing niche and prefer to cut ties with the central government. Faced with the threat and imminent danger of separation insurgencies equipped with military supplies, the central government has run out of options, but the military oppression. Lack of experiences, skills, and training surely can not cope with the highly ones of the Indonesian military personnel, though with obsolete military weapons. The man behind the gun that matters.As the combatants are the same citizens, reconciliation between the brotherly belligerents must have been made. Power struggle must have been Carried out in a fashion as humanly possible. Election in either national or regional scale have Become the main battlefield. Today, it's not the blood that shed, but the money that must have been poured in a very large sum to win the election. As the members of any given political party, they must fully comply and obey with what would have been set as the rules, objectives, and interests of Reviews their political party.